Surgical Repair of Hypermobile Lateral Meniscus Secondary to Popliteomeniscal Fascicle Tears Improves Pain and Mechanical Symptoms - Malik E. Dancy, M.D; Adam J. Tagliero, M.D; Sara E. Till, M.S; Daniël B. Saris, M.D., Ph.D; Bruce A. Levy, M.D; Christopher L. Camp, M.D; Aaron J. Krych, M.D (Elsevier, 2023)
Purpose: To describe the clinical and radiographic features associated with isolated hypermobile lateral meniscus (HLM), and report patient outcomes following surgically repaired isolated HLM. Methods: All patients diagnosed with HLM from 2000 to 2020 at a single academic institution were identified and reviewed. Patients were excluded if they had concomitant ligament injury or lacked 2-year follow-up. Preoperative and postoperative visual analog scale (VAS) pain scores were determined from clinical notes. Statistical analysis was performed in JMP, and statistical significance was determined with use of a paired t-test. Results: Eighteen knees in 17 patients met inclusion criteria. Mean patient age was 24.1 (range: 6-61) years. Mean follow-up was 73 months (25-151 months). All 18 knees reported pain at presentation; 94% (17/18) had mechanical symptoms. All 18 knees had preoperative MRIs, but only 1 (5.6%) knee was correctly diagnosed by a musculoskeletal trained radiologist. Most repairs were performed with an all-inside technique (61%, 11/18). VAS score improved significantly from 7.2 ± 2.9 preoperatively to 0.7 ± 1.9 postoperatively, with average improvement of VAS score of 6.5 (P < .001). Only one (5.6%) knee required revision meniscal surgery. Conclusions: Hypermobile lateral meniscus patients commonly see multiple providers, fail to have their HLM diagnosed on MRI, and undergo various treatments prior to a successful diagnosis. Localized lateral joint line pain, mechanical symptoms, and absence of distinct meniscus tear on MRI are the most frequent clinical presentations. Surgery with meniscus repair is a reliable solution to improve pain and mechanical symptoms. Level of Evidence: Level IV, therapeutic case series.